The Effect of Applying the Learning Cycle Learning Model on Students' Learning Outcomes of Geography - Ari Whudian; Yongha Park; Raphael Ane Atanga (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: The aims of this study were: 1) To compare the results of learning Geography of students using the Learning Cycle 7E learning model, Learning Cycle 5E with the Expository. 2) Comparing the results of learning Geography of students using the Learning Cycle 7E learning model with the Expository. 3) Comparing the results of learning Geography of students using the Learning Cycle 5E learning model with the Expository. 4) Comparing the results of learning Geography of students using the Learning Cycle 7E learning model with Learning Cycle 5E. Methodology: This study uses a Quasi-Experimental method with a